Seasonal and gestational variation in perinatal depression in a prospective cohort in New Zealand. (29th October 2018) - Chan, Johanna E.; Samaranayaka, Ari; Paterson, Helen
Abstract : Background: Perinatal depression has wide‐ranging impacts on the health of mothers, babies and their families. Previously published data suggest seasonal variation in the prevalence of perinatal depression, as well as possible variation with gestation. Aims: To describe the prevalence of perinatal depression in a New Zealand population; to describe the trend in depression over gestational age; and to assess the influence of season on perinatal depression. Materials and Methods: We performed a secondary analysis of data from a prospective cohort of 260 women in Dunedin, New Zealand. Edinburgh Depression Scores were collected at four antenatal time points and at six months postpartum. Results: Prevalence of depression decreased from 8.1% to 4.6% antenatally, and to 6.6% postnatally, but the variation was non‐significant. Prevalence was significantly higher in winter and spring antenatally (odds ratio (OR) 3.15, 95% CI 1.01–9.82 and OR 3.16, CI 1.05–9.55), and in spring postnatally (OR 8.40, 95% CI 1.01–69.52) compared to autumn. Antenatal depression was associated with poor sleep quality (OR 4.27, 95% CI 1.22–14.93), while postnatal depression was associated with caesarean delivery (OR 5.03, 95% CI 1.29–19.64). Conclusions: This is the first NZ cohort to assess depression over multiple antenatal and postnatal time points. A significantly higher rate of depression was identified in winter and spring antenatally and in spring postnatally, corresponding to a higher risk of postnatal depression with autumn deliveries. These findings should prompt greater awareness at these higher risk time periods.